Analysis of Public Service Management of the Youth and Sports Education Service during the Pandemic Period - Mohamad Ali Erfanto; Ferry Khusnul Mubarok; Yuli Haryati; Johan Arifin (At-Taqaddum, 2022)
The existence of a pandemic has had an impact on the quality of public services in various institutions, which has caused a decrease in satisfaction due to various changes. The purpose of this study was to analyze management and determine the level of satisfaction with public service management carried out by staff of the institutional and infrastructure division of Early Childhood Education and Non-Formal Education at the Youth and Sports Education Office of Rembang Regency. District during a pandemic. The method used in this study is descriptive, by first analyzing the results of the questionnaire qualitatively, while the results of the interviews are presented descriptively. There are two data collection techniques used, namely by giving questionnaires and by conducting interviews. From this study it was found that indicators of achievement in knowing the level of community satisfaction can use measurements from five dimensions, namely responsiveness, reliability or reliability, assurance or certainty and certainty, empathy, and tangible or physical evidence. The conclusion that can be drawn is that management in public services is very important in the delivery of services, guided by these five dimensions, public service providers are expected to be able to improve services in order to create comfortable conditions for the community as service recipients.